NEIGHBORS, CITIZENS AND PATRIOTS: THE COMITÉS PATRIÓTICOS AND THE SPATIOTEMPORALITY OF OPPOSITION TO NEOLIBERALISM IN COSTA RICA - Rayner, Jeremy (2013)
The Comités Patrióticos emerged in the context of the historic referendum on the Free Trade Agreement with the United States. This paper offers an analysis of this movement based on a year of ethnographic research. I focus on questions of spatiotemporality and political scale, in order to illuminate how this movement has attempted, during and after the referendum, to articulate a new political structure capable of acting at once on local and national scales in order to challenge the neoliberal project.